The great masters - Menpes, Mortimer, 1855-1938; Menpes, Mortimer, 1855-1938; National Library of Australia. Exhibitions (Canberra, A.C.T. : National Library of Australia, 2002)
Advertising an exhibition at the National Library of Australia from 25 July - 7 October 2002 titled The great masters by Mortimer Menpes. Depicts a facsimile of a portrait etching entitled Chapeau de paille.
Caption title.
Keywords: Menpes, Mortimer, -- 1855-1938 -- Exhibitions; National Library of Australia -- Posters; Art, Australasian -- 20th century -- Exhibitions; Library exhibits -- Australia -- Posters; Artists -- Australia -- 21st century -- Exhibitions; Posters, Australian; Australia -- Posters; Australian